The conjugating green alga Zygnema sp. (Zygnematophyceae) from the Arctic shows high frost tolerance in mature cells (pre-akinetes) - Trumhová, Kateřina; Holzinger, Andreas; Obwegeser, Sabrina; Neuner, Gilbert; Pichrtová, Martina (Protoplasma, 2019)
Green algae of the genus Zygnema form extensive mats and produce large amounts of biomass in shallow freshwater habitats. Environmental stresses including freezing may perturb these mats, which usually have only annual character. To estimate the limits of survival at subzero temperatures, freezing resistance of young Zygnema sp. (strain MP2011Skan) cells and pre-akinetes was investigated. Young, 2-week-old cultures were exposed to temperatures of 0 to - 14 °C at 2-K steps, whereas 8-month-old cultures were frozen from - 10 to - 70 °C at 10-K intervals. Cell viability after freezing was determined by 0.1% auramine O vital fluorescence staining and measurements of the effective quantum yield of photosystem II (ФPSII). At - 8 °C, the young vegetative cells were unable to recover from severe frost damage. But temperatures even slightly below zero (- 2 °C) negatively affected the cells' physiology. Single pre-akinetes could survive even at - 70 °C, but their LT50 value was - 26.2 °C. Severe freezing cytorrhysis was observed via cryo-microscopy at - 10 °C, a temperature found to be lethal for young cells. The ultrastructure of young cells appeared unchanged at - 2 °C, but severe damage to biomembranes and formation of small foamy vacuoles was observed at - 10 °C. Pre-akinetes did not show ultrastructural changes at - 20 °C; however, vacuolization increased, and gas bubbles appeared at - 70 °C. Our results demonstrate that the formation of pre-akinetes increases freezing resistance. This adaptation is crucial for surviving the harsh temperature conditions prevailing in the High Arctic in winter and a key feature in seasonal dynamics of Zygnema sp.
Keywords: Live cell staining; Auramine O; Ice; zmrazování; Ultrastructure; chlorofyl; Arktida; Arctic Regions; Chlorophyll fluorescence; Freezing; Chlorophyll